Undertreatment of nausea and other symptoms in hospitalized cancer patients - Greaves, J.; Glare, P.; Kristjanson, Linda; Stockler, M.; Tattersall, M. (Springer, 2009)
Objective This survey aimed to provide a symptom profile, in particular for nausea and its treatment, of advanced cancer patients prior to implementation of a clinical practice guideline for nausea. Materials and methods An audit of 82 advanced cancer patients admitted to a major Australian teaching hospital was undertaken. While nausea was present in 26 (32%) of respondents, antiemetics were prescribed in 52 (68%), a higher proportion than in the past, and being taken by 32 (39%). Results and conclusion Patients reporting moderate-to-severe nausea often missed out on treatment. These findings underscore the need for more attention to education of hospital staff in the assessment and treatment of this frequently bothersome symptom, and raise issues for study design of symptom control research.